Poison - Wooding, Chris, 1977- (Orchard Books, 2005)
When Poison leaves her home in the marshes of Gull to retrieve the infant sister who was snatched by the fairies, she and a group of unusual friends survive encounters with the inhabitants of various Realms, and Poison herself confronts a surprising destiny.